Strategies of Islamic Religious Education Teachers in Guiding Prayer Practices in Darussalam Integrated Islamic Elementary School - Hariadi Hariadi; Fauziah Zainuddin; Mustaming Mustaming (State Islamic Institute of Palopo, 2022)
This article discusses the Strategy of Islamic Religious Education Teachers in Guiding Prayer Practices in Darussalam Integrated Islamic Elementary Schools. The main topics of discussion in this study are: How is the implementation of coaching the practice of prayer to students at the Darussalam Integrated Islamic Elementary School? How is Islamic Religious Education teachers' strategy in fostering prayer practice at the Darussalam Integrated Islamic Elementary School in Palopo City? How are the obstacles and solutions given by the Religious Education teacher Islam in fostering the practice of prayer at the Darussalam Integrated Islamic Elementary School, Palopo City? This study aims to: determine the implementation of coaching students' prayer practice; knowing the strategy of Islamic Religious Education teachers in fostering students' prayer practice; knowing the obstacles and solutions for Islamic Religious Education teachers in fostering the practice of prayer at the Darussalam Integrated Islamic Elementary School, Palopo City. This research is descriptive qualitative research that uses a pedagogical and psychological approach. The author uses data collection techniques, among others, by making direct observations at the author's research location, interviewing Islamic Religious Education teachers, staff, and students, making documentation and collecting school documents, data analysis, data reduction, triangulation techniques, and presenting data and drawing a conclusion. The results of this study indicate that the development of the practice of prayer for students at the Darussalam Integrated Islamic Elementary School in Palopo City runs as much as possible by using the strategy of Islamic Religious Education teachers, namely by providing prayer guidance materials through the provision of materials and direct practice as well as students and teachers correcting reading errors and the student prayer movement, the obstacle faced by Islamic Religious Education teachers is the lack of parental supervision of students in participating in the current face-to-face learning program. The solution is to provide controlled learning both from school and from home to students by collaborating with parents of students and carrying out very strict health protocols.